The Dramatic Prologues of Alexander Nowell: Accommodating the Classics at 1540s Westminster. (17th May 2017) - Lazarus, Micha
ABSTRACT: Alexander Nowell, headmaster of Westminster, left a rough manuscript notebook that contains Latin prose prologues to three classical plays performed by his pupils at Westminster in the 1540s: Terence's Adelphoe and Eunuchus, and Seneca's Hippolytus . These prologues, a substantial new source in Reformation criticism, are transcribed and translated in full here for the first time, and placed in their historical, literary, and intellectual context. Prefacing Terence's comedies, Nowell produces a learned and charismatic address in the Erasmian mode, drawing together a range of pragmatic and theoretical defences of comedy and a robust notion of fictionality remarkable at this early date. His treatment of Seneca's Hippolytus is quite different: Nowell draws a detailed and unusual parallel between the classical myth and the scriptural story of Joseph and Potiphar's wife that relates him closely to contemporary developments in Reformation neo-classicism in Germany and the Low Countries. These multi-faceted orations paint a complex picture of pedagogy, bureaucratic necessity, and literary thought in the early morning of the English Reformation. 1